“It doesn’t matter if we’re the most amazing professionals in the world…” A qualitative study of professionals’ perspectives on parent-child interaction assessment with deaf infants - Curtin, Martina; Wakefield, Tina; Herman, Rosalind; Morgan, Gary; Cruice, Madeline (Frontiers in Psychology, 2024)
Introduction: Parent child interaction (PCI) is positively associated with deaf children's language development. However, there are no known, deaf-specific tools to observe how a parent interacts with their deaf child aged 0-3 years. Without a framework for professionals to use with families, it is unknown how professionals assess PCI, what they assess, why they assess, and how the assessment results relate to case management. Methods: Eighteen hearing and deaf professionals, who work with deaf and hard of hearing infants aged 0-3 years and their families, attended online focus groups. The aim of the study was to gain insight into the professional assessment of PCI. Data were analysed using thematic analysis. Findings: Six themes were generated from the dataset. Professionals discussed how central parents were in the support offered to families in the home, the importance of knowing and understanding the individual family, and accounting for and supporting parental well-being. Descriptions on how to administer a best practice PCI assessment included which parent behaviours to assess and how to make adaptations for different populations. Professionals shared how the assessment and review process could be used to inform and upskill parents through video reflection and goal setting. Discussion: This study provides insight into the mechanisms and motivations for professionals assessing the interactive behaviours of parents who have deaf children aged 0-3. Professionals acknowledged that family life is multi-faceted, and that support is most meaningful to families when professionals worked with these differences and incorporated them into assessment, goal setting, and intervention plans.